Psychological Barriers to Satisfaction of Reproductive Health Needs of the Age-Cohort 10-24 Years in Imo State, Nigeria - J. U. , Ogbalu; Oparah , J.S.; M. N., Fidelis; C.C. , Mgbeahurike (African Journal of Education,Science and Technology (AJEST), 2017)
This study sought to investigate psychological barriers to satisfaction of reproductive health needs of the age-cohort 10-24 years in Imo State, Nigeria. To facilitate the realization of this objective, three research questions and two hypotheses were postulated for the study. The population for the study was 93,250 which comprised of students in secondary and tertiary institutions in Imo State. Using the multi-stage sampling procedure, a sample size of 5010 students was drawn. The sample size represented 5 per cent of the population. The study adopted cross-sectional survey research design. The instrument used for data collection was a self-constructed questionnaire, known as PSYBARNAC which contained 13 items in two sections A & B. Section ‘A’ contained the personal data (age and gender) of respondents while section ‘B’ contained the psychological barriers to satisfaction of reproductive health needs. The instrument was validated by a jury of 3 experts drawn from the department of Physical and Health Education, Alvan Ikoku Federal College of Education, Owerri. The reliability co-efficient of 0.88 was derived using Pearson Product Moment Reliability co-efficient. The data obtained was analyzed using descriptive statistics of percentage and mean in answering the research questions while inferential statistic of Z-test and ANOVA were used to test the hypotheses at 0.05 level of significance. The result showed that young persons are faced with psychological barriers to reproductive health needs. The findings further revealed that the psychological barriers experienced by age cohort 10-24 years vary by different age groups and gender. Based on the findings of the study, the investigators recommended that, the government through the Ministry of Education and Health should package a sex education programme for young persons of varying age and other status (gender, sexual activity).